Sustainable chemical synthesis using singlet oxygen - Miller, Samuel Jacob (2019)
This Thesis describes the use of photochemically generated singlet oxygen as an efficient, low waste oxidant for Greener chemical processing. Chapter 1 provides background on Green Chemistry and Process Chemistry. Strategies for improving the efficiency of multi-step chemical syntheses are discussed, including the use of continuous flow chemistry. Literature examples are given which highlight the process benefits of the examined strategies. A detailed review of singlet oxygen chemistry is also provided, focusing on the mechanism and synthetic utility of reactions of singlet oxygen with organic substrates. This Chapter also sets down the general aims for the work included in this Thesis. The first synthetic Chapter 2 centres on attempts to improve a pre-existing process for the synthesis of an important antimalarial compound artemisinin – one of the few examples of an industrial-scale application of singlet oxygen. Unusual aqueous solvent systems are assessed as a way to reduce the quantity of hazardous waste produced, and continuous flow chemistry is applied in an attempt to improve material throughput, all in an attempt to lower the cost and environmental impact of artemisinin production. Chapter 3 describes the development of direct monitoring techniques combining flow photochemistry and nuclear magnetic resonance spectroscopy with a view to studying the mechanism of the artemisinin synthesis. Chapter 4 presents work towards the use of singlet oxygen in a concise, divergent synthesis of a novel family of natural products, the Glaciapyrrols. Several members of this family show therapeutic potential as anti-cancer agents. Singlet oxygen is assessed as an efficient way to install these compounds’ many oxygen-containing functional groups in a step economic manner. Finally, Chapter 5 provides experimental detail for the methods and Equipment used in this Thesis, and Chapter 6 considers the extent to which the Thesis aims have been fulfilled, placing the work herein within the wider context of Green Chemistry and Process Chemistry research.